2006
DOI: 10.1159/000090655
|View full text |Cite
|
Sign up to set email alerts
|

Heredity: A Prognostic Factor for Acne

Abstract: Background: The role of heredity in acne severity and therapeutic response remains unclear. Objective: A prospective epidemiologic study was performed to compare clinical and evolutive features of acne and response to treatment in 151 patients with acne with (A+) or without (A–) family history of acne. Methods: A+ and A– patients were compared on clinical and therapeutic criteria. A+ patients were then distributed into subgroups (M+, F+, M+F+) following the origin of family history (father: F, mother: M). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 28 publications
7
49
2
1
Order By: Relevance
“…Previous studies showed that moderate to severe acne were strongly associated with firstdegree relative's acne history [5] [19]. Students in our study with moderate to severe acne had a higher percentage of sibling's history of 95.2%.…”
Section: Discussionsupporting
confidence: 47%
“…Previous studies showed that moderate to severe acne were strongly associated with firstdegree relative's acne history [5] [19]. Students in our study with moderate to severe acne had a higher percentage of sibling's history of 95.2%.…”
Section: Discussionsupporting
confidence: 47%
“…There has previously been some evidence that acne is an inherited disease [16, 17]. The detailed mode of inheritance remains unproven; however, it is most likely polygenic, and genetic factors, Propionibacterium acnes infection, production of inflammation and environmental influences are involved in the etiology of acne [2].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that acne is an inherited disease [1,22,23,24]; for example, an adult twin study confirmed that acne is a highly heritable disease [25]. Many studies support this point.…”
Section: Discussionmentioning
confidence: 95%